The Coordinated Direct Investment Survey Guide 2015 - Mesias, Rita (Manuals and Guides, 2015)
This Coordinated Direct Investment Survey Guide (Guide) has been prepared to assist economies in participating in the Coordinated Direct Investment Survey (CDIS). The CDIS is being conducted under the auspices of the Statistics Department of the IMF across a wide range of economies. The survey is conducted simultaneously by all participating economies; uses consistent definitions; and encourages best practices in collecting, compiling, and disseminating data on direct investment positions. The CDIS is thus an important tool in capturing world totals and the geographic distribution of direct investment positions, thereby contributing to important new understandings of the extent of globalization, and improving the overall quality of direct investment data worldwide. As of the writing of this updated Guide, more than 100 economies participate in the CDIS.